Ethnobotanical survey of medicinal plants for bone fracture treatment in Lingmoo, Sikkim - Chettri, Bhumika; Khar, Tiewlasubon Uriah; Bhutia, Sonam (Journal of Applied Pharmaceutical Research, 2025)
Background: This study documents the use of herbal plants by traditional healers in Lingmoo, Namchi district, Sikkim, to treat bone fractures. Methodology: The methodology used were survey-based, pre-structured questionnaire, field investigation and face to face interaction with one traditional healer. We have recorded about 29 ethno-medicinal plants naturally available in the selected area. Results: According to the survey results, a total of 29 numbers of ethnomedicinal plant species belonging to 23 different families (Rosaceae topped the list) were identified and summarized in Table 1. The study revealed that herbs (48%) are mainly used, followed by trees (24%), climbers (17%), and shrubs (11%). In case of frequency of use, these plants were highly cited during the interview: rivularis, Kaempferia rotunda, Viscum articulatum, Urtica dioica, Curcuma longa, Lepidium sativum, Beaumontia grandiflora, Bergenia ciliate, and Laportea bulbifera. The parts used were roots, stem barks, whole plants, and seeds. The most commonly used preparation was paste. According to gender-wise comparison, males (60%), females (25%), and children (15%) were getting the treatment. Out of 29 plant species, 12 species are abundant and, 1 is in threatened condition; only 3 species are cultivated in present days. Conclusion: Documentation of local plants used by a specific traditional healer will benefit the sustainable use of indigenous medicinal plant practices. It will also provide preliminary information for future biological resource management and research development, which will eventually help in the conservation of ethnomedicinal plants and the advancement of such ideas.